Combination of stearic acid coated magnetic nanoparticle based sonication assisted dispersive solid phase extraction and slotted quartz tube-flame atomic absorption spectrophotometry for the accurate and sensitive determination of lead in red pepper samples and assessment of green profile. (15th January 2020) - Zaman, Buse Tuğba; Erulaş, Ahmet Fatih; Chormey, Dotse Selali; Bakirdere, Sezgin
Graphical abstract: Highlights: Environmentally friendly method was developed for determination of trace lead in red pepper samples. Toxic solvent usage was inhibited with the use of a sorbent. Lead was determined at trace levels with a new preconcentration technique. The enhancement factor in detection power was obtained as about 31 folds. Satisfactory percent recovery results between 102 and 107% was obtained in red pepper samples. Abstract: This study describes the determination of lead at trace levels by slotted quartz tube flame atomic absorption spectrophotometry (SQT-FAAS) after preconcentration by the help of stearic acid coated magnetic nanoparticle (SAC-MNPs) based sonication assisted dispersive solid phase extraction (SA-DSPE). SAC-MNPs were used due to their easy separation advantages by the application of external magnetic field. All extraction parameters were optimized by response surface methodology based experimental design. The experimented data was evaluated by the analysis of variance. Under the optimum conditions, about 31 folds enhancement in detection power was obtained over the conventional FAAS. The recovery results obtained for samples spiked at 60 and 120 ng mL −1 were 106.6 and 102.6%, respectively, validating the method as accurate and applicable to the red pepper matrix. The percent relative standard deviations of the results were under 5.0% even at low concentrations that established high precision for replicate extractions and instrumental readings.